1982
DOI: 10.3758/bf03202440
|View full text |Cite
|
Sign up to set email alerts
|

Automatic phonological priming in visual word recognition

Abstract: reported by Hillinger (1980, Experiment 3). He used a priming technique in which subjects made a lexical decision about visual prime-and target-letter strings. In a test that assessed whether phonological information is automatically accessed, performance when targets were primed by phonologically similar but graphemically different words (e.g., EIGHT-MATE) was compared with performance when primes were neutral (e.g., ******-MATE). Hillinger found that, relative to the neutral-prime baseline, lexical decisions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
160
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(169 citation statements)
references
References 26 publications
(38 reference statements)
9
160
0
Order By: Relevance
“…Indeed, Humphreys and Evett (1982) suggested that phonological priming effects result from feedback from the lexical level. They found that identification accuracy was better for targets that were presented after phonologically related primes (e.g., SHOOT -CHUTE), compared to prime target pairs that were only orthographically related (e.g., SHOOT -SHORT) or unrelated pairs (e.g., SHOOT -TRAIN).…”
Section: Phonological Effects In Behavioral Studiesmentioning
confidence: 99%
“…Indeed, Humphreys and Evett (1982) suggested that phonological priming effects result from feedback from the lexical level. They found that identification accuracy was better for targets that were presented after phonologically related primes (e.g., SHOOT -CHUTE), compared to prime target pairs that were only orthographically related (e.g., SHOOT -SHORT) or unrelated pairs (e.g., SHOOT -TRAIN).…”
Section: Phonological Effects In Behavioral Studiesmentioning
confidence: 99%
“…Geoffrey Loftus, Mark Reinitz, and an anonymous reviewer provided constructive criticism of an earlier version of this article. Correspondence concerning this article should be addressed to L. Ferrand, Laboratoire de Psychologie Experimentale, 28 rue Serpente, 75006 Paris, France. repetition (or identity) priming when a prime word is masked and unavailable for conscious report in tasks such as lexical decision (Forster & Davis, 1984;Segui & Grainger, 1990a, 1990bSereno, 1991), speedednaming (Forster & Davis, 1991;Sereno, 1991), and perceptual identification (Evett & Humphreys, 1981;Humphreys, Besner, & Quinlan, 1988;Humphreys, Evett, & Taylor, 1982).…”
Section: Repetition Priming In Word and Object Namingmentioning
confidence: 99%
“…In word recognition, a large amount of evidence indicates that phonological information plays an early and automatic role in the recognition of printed words (e.g., Lukatela & Turvey, 1994;Perfetti & Bell, 1991;Perfetti, Bell, & Delaney, 1988;Peter & Turvey, 1994;Rayner, Sereno, Lesch, & Pollatsek, 1995;Ziegler & Jacobs, 1995;Ziegler, Van Orden, & Jacobs, 1997; for a review, see . Some of this evidence comes from priming studies in which phonological overlap between a prime and a target facilitates recognition of the target (e.g., Ferrand & Grainger, 1992, 1993Humphreys, Evett, & Taylor, 1982;Lukatela, Frost, & Turvey, 1998). Moreover, studies that manipulated prime duration point to the possibility that orthographic and phonological processes follow different time course with orthographic information being accessed slightly faster than phonological information (e.g., Ferrand & Grainger, 1993; see also Perfetti & Tan, 1998).…”
mentioning
confidence: 99%